Method for calculating a water surface profile at the watershed scale with little observed data based on ASTER GDEM: a case study in the Naoli River, northeast China - Tian, Lin; Wei, Yinying; Wang, Sheng; Zhang, Guorong; Zhao, Chuangjia; Huang, Xin; Huang, Weiyu (Frontiers in Environmental Engineering, 2024)
The calculation of river water surface profile has always been a very important problem in the field of hydraulic engineering. With the development of the research on the surface and ground water coupled simulation, river water surface profile become an indispensable boundary condition for simulating the inter-relationship between surface and ground water. River channel large-section data is the basic condition for building most hydrodynamic models, and its field data often consumes a lot of manpower and material resources. We extracted river sections using ArcGIS based on the ASTER GDEM data; interpolated the corresponding water level of different guarantee rate flow in Baoqing station and Caizui station. We analyzed the variation of upstream water level under different Manning coefficients n, and the bed resistance of the Naoli river was determined to be 0.025. In order to ensure the rationality of the model and the reliability of the operation results, three indexes (non-scouring velocity, the shear stress of river bed and water surface slope) are used to analyze and test the rationality of the simulation results. Ultimately, achieved the calculation of water surface profile from Baoqing hydrologic station to Caizuizi hydrologic station in Naoli river through MIKE11 hydrodynamics model under the guaranteed rates of 20%, 50%, 75%, and 95% of the flow.The calculation of the water surface profile can provide the hydrological boundary conditions for surface and ground water conversion and the combined simulation. Furthermore, the present study can provide a feasible method for calculating river water surface profile in areas lack measured section data.